2014
DOI: 10.1111/1467-8268.12083
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Finance–Growth Nexus in Sub‐Saharan Africa: Results from Error Correction‐based Panel Cointegration Tests

Abstract: This paper re-examines the long-run finance-growth nexus in sub-Saharan Africa (SSA) using data from 17 countries over the period . We apply error correction-based panel cointegration tests that take into account crosssectional dependence among countries. Our resultsunlike a previous study using the same dataindicate the existence of a long-run relationship between financial and economic development in SSA countries. Moreover, our results clearly show that the long-run causality runs from financial to economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
(116 reference statements)
2
14
0
Order By: Relevance
“…These findings are consistent with Walle () who reported that financial development accelerates economic growth in sub‐Saharan Africa. Kouki () also reported that financial development enhances economic growth in the North African region.…”
Section: Resultssupporting
confidence: 92%
“…These findings are consistent with Walle () who reported that financial development accelerates economic growth in sub‐Saharan Africa. Kouki () also reported that financial development enhances economic growth in the North African region.…”
Section: Resultssupporting
confidence: 92%
“…Although a large amount of literature has examined the impact of financial development along various dimensions of economic development, namely: inequality (De Haan & Sturm, 2017), poverty reduction (Uddin, Shahbaz, Arouri, & Teulon, 2014; Abosedra, Shahbaz, & Nawaz, 2016), productivity (Moretti, 2014), innovation (Ferreira, Manso, & Silva, 2012), and most importantly economic growth (Ghirmay, 2004; Kouki, 2013; Walle, 2014), not too many studies focus on the link between financial development and the informal economy. Theoretically, financial development might affect the informal economy through several channels.…”
Section: Introductionmentioning
confidence: 99%
“…Financial sector development has long been recognized as one of the key drivers of economic growth (Ghirmay, ; Beck and Hesse, ; Kouki, ; Walle, ). Financial innovations have been a major driver of financial inclusion and financial sector development (Demirguc‐Kunt et al ., ).…”
Section: Introductionmentioning
confidence: 99%